The Scale for Assessing Sensitivity of the Oral-Facial Complex (Orofacial) in evaluating feeding disorders in children from birth to 3 years of age - Wisniewska, Marta; Kaczyńska, Aleksandra (Logopedia Silesiana, 2024)
The aim of the study was to provide a reliable tool for identifying feeding problems in children from the first month of life up to three years old. This tool is the Scale for Assessing Sensitivity of the Oral-Facial Complex (SASOFC), which consists of two subscales: Sensory Hypersensitivity and Oral Functions, Anatomy, and Functioning of Articulatory Organs. The first subscale is completed by a specialist based on an interview with the child’s parents or caregivers. The assessment using the second subscale is conducted through a physical examination of the child. Construct validity was established in a study of 305 children aged 0–3 years. The normative sample (n = 153) and the clinical sample (n = 152) were recruited from daycare centers. Comparison of the mean scores between the normative and clinical samples achieved high significance in both subscales. The scale also demonstrates high reliability indices (test-retest 0.99; α = 0.96) and validity (Fleiss’ κ 0.65). Based on the obtained results, percentile norms corresponding to the sample were constructed. We conclude that the Scale for Assessing Sensitivity of the Oral-Facial Complex (SASOFC) is an important and reliable tool suitable for assessing sensory-based feeding problems in young children, in both research and diagnostic settings.